ANALISIS PENGARUH DAYA KELUARAN PANEL SURYA MENGGUNAKAN REFLEKTOR (CERMIN) DENGAN PENAMBAHAN SISTEM PENDINGIN HEATSINK - Yusuf Prawiro Samudro, (2021)
The addition of a reflector to the solar panel is used to increase the intensity of sunlight received by the solar panel so that the electric power generated by the panel increases. In adding a reflector to a solar panel, several factors must be considered in order to increase the power produced without having a negative effect on the solar panel, one of which is to provide a cooling system. So research is needed to increase the power generated by solar panels and a suitable cooling system to overcome the rising temperature due to the addition of a reflector. The research was conducted by varying the glass mirror reflector, aluminum foil reflector, the angle of the reflector, and the heatsink cooling system. The research method used in this study is to compare 2 models of solar panels, namely: a solar panel with the addition of a glass mirror / aluminum foil reflector and a heatsink cooling system, and a solar panel model without any additions. The results show that the solar panel model with the addition of a glass / aluminum foil mirror reflector can increase the output power according to the angle of the reflector, the highest increase reaches 16.70% in the 450-angle aluminum foil mirror reflector.The heatsink cooling system is considered to function to reduce the temperature of the solar panels. but the decrease is small below 5%. Keyword : Power, Output, Solar Panel, reflector, heatsink